New Proposals for the Design of Integrated Online Wine Industry Dictionaries - Leroyer, Patrick (Lexikos, 2013)
The specialised lexicographic treatment of oenology and viticulture usually consists in the compiling of articles describing the language of wine in general language dictionaries, or presenting professional knowledge of wine in specialised multi-field dictionaries and encyclopedias. This treatment also encompasses the terminological compilation of single field dictionaries describing the language and/or knowledge of wine. Lexicographically speaking, all this is but a fraction of the complete picture. Indeed, the specialised lexicography of oenology and viticulture is multifaceted and goes far beyond the above-mentioned types of articles and dictionaries. It includes a broad range of both online and printed lexicographically structured information tools, such as wine guides, atlases, companions, oenological websites, and mobile applications. In line with this growing interest for lexicographically structured information tools on oenology, wine making, and wine tasting, this article argues for an expansion of lexicography dealing with wine: It explains how a new lexicographic information tool, in this case OENOLEX Burgundy, a French monolingual online wine dictionary commissioned by the Burgundian wine industry, offers various functions and usage modes to its users, including access to multimodal data, and how it differs from a comparable South African online wine dictionary commissioned by the South African wine industry. In line with the findings of this comparative study, lexicographic proposals are subsequently formulated. The first proposal is that such online wine industry dictionaries should be developed in accordance with specific user situations and needs, and make use of a monofunctional design and an adaptive user interface. The second proposal is that such online wine industry dictionaries should not stand alone, as they could benefit from a full integration with the websites of the wine industry, and consequently transform into genuine lexicographic information tools. Keywords: specialised lexicography, specialised dictionaries, online specialised dictionaries, subject-field-based dictionaries, user-situation-based dictionaries, function theory of lexicography, wine industry dictionaries, consultation, navigation, access modes, multimodality, user needs paradigm, website integration